Cultivation of nile tilapia (oreochromis niloticus) in net pens: a review of the literature - Romanzini, Gabriel de Brito (2023)
The culture of Oreochromis niloticus, popularly known as tilapia, in net-tanks has shown to be an activity of high zootechnical index in pisciculture, evidencing attractive economic, social, and environmental gains. The current pisciculture is configured as a modern and technified activity, demanding planning, application of scientific and market knowledge. Currently, Brazil ranks fourth in the world in the cultivation of the species and, only in 2020, 486,155 tons of this freshwater fish were produced. The net-tanks are closed with screens, covers, feeders, and floats, and various types of materials can be used. These places must present the characteristics of durability, lightness, ease of water renewal, resistance to corrosion and to colonization by algae, mollusks, and other organisms, besides being safe for the fish and operators, and low cost. O presente estudo, ao realizar um levantamento bibliográfico à volta da temática, promove uma abordagem sistemática dos principais aspectos que envolvem a atividade e permite que produtores e profissionais possam compreender melhor os métodos de inserção e utilização do sistema em sua propriedade, bem como a avaliação da viabilidade técnica e econômica dos projetos de piscicultura em tanques-rede, considerando as características fisiográficas, climáticas e econômicas específicas de cada região.